Is the Level of Pentraxin-3 a Valid Biomarker in Axial Spondyloarthritis? - Orucoglu, Nurdan; Balci-Fidanci, Senay; Tamer, Lulufer (Aktuelle Rheumatologie, 2023)
Background Pentraxin-3 (PTX-3) is essential in inflammation, remodelling and regulation of inflammation in various rheumatic diseases. This study aimed to determine whether serum PTX-3 levels indicate increased inflammation and disease activity in patients with axial spondyloarthritis (AxSpA).Material and Methods The study comprised 50 AxSpA patients and 20 healthy controls (HC). Serum PTX-3, interleukin (IL)-17 and IL-23 levels were compared between AxSpA patients and the control group. The relationship between PTX-3 levels and acute-phase reactants and disease activity was examined. Disease activity was scored using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the Ankylosing Spondylitis Disease Activity Score-CRP (ASDAS-CRP). Patients with AxSpA were also separated into two subgroups – non-radiographic AxSpA (nr-AxSpA) and radiographic AxSpA (r-AxSpA) – and compared based on their PTX-3 levels. PTX-3, IL-17 and IL-23 levels were measured using the enzyme-linked immunosorbent assay method.Results PTX-3 levels were higher in patients with AxSpA compared with the HC (2.69±2.03 vs 1.84±1.03 ng/mL, p=0.025). When patients were divided into nr-AxSpA and r-AxSpA subgroups, this difference was found to be only due to patients with r-AxSpA. The r-AxSpA group had significantly higher PTX-3 levels than the nr-AxSpA and HC groups (p=0.020 and p=0.016, respectively). There was no statistically significant difference in PTX-3 levels between the nr-AxSpA and HC groups (p=0.961). There was no correlation between PTX-3 levels and acute-phase reactants, IL-17, IL-23 and disease activity scores (BASDAI and ASDAS-CRP).Conclusion These findings support the hypothesis that PTX-3 levels are higher in patients with r-AxSpA, where chronic inflammation and structural progression are more pronounced and can be used as an inflammation marker. However, they demonstrate that this relationship does not exist in nr-AxSpA and that there is no correlation between disease activity and PTX-3 levels. Thus, PTX-3 levels may be associated with structural changes.
Keywords: Pentraxin-3; inflammation; interleukin; disease activity; axial spondyloarthritis